Design and Development of an Android-based Rentak Bulian Dance Adventure Role-Playing Game using a Story-Driven Approach and Quest System - Panji Rachmat Setiawan; Syefriani Syefriani; Ichsan Alfarezi; Mario Nur Rohman (Sistemasi: Jurnal Sistem Informasi, 2026)
The low level of engagement among younger generations in learning local culture has created a need for interactive and structured cultural introduction media. This study designs and develops a prototype of an Android-based RPG adventure game featuring the Rentak Bulian Dance using a story-driven approach and quest system as a progressive structure for delivering cultural content in stages. The research employed the Research and Development (R&D) method using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation), integrated with the Game Development Life Cycle (GDLC) framework to ensure process traceability throughout the game development stages. The product implements several core components, including a story module, dialogue system, quest manager, quest log, and reward/feedback mechanisms, while formalizing missions through a quest tree structure consisting of main quests and side quests. The feasibility evaluation was conducted using the System Usability Scale (SUS) involving 30 respondents. The results showed an average SUS score of 76.0 (SD = 5.9; min = 65.0; max = 87.5), with 93.3% of respondents classified within the acceptable category (≥70). These findings indicate that the prototype is feasible as a medium for introducing the Rentak Bulian Dance, with recommendations for improvement focusing on the clarity of mission instructions and navigation consistency. The main contribution of this study lies in the integration model between narrative and quest systems for cultural content delivery, as well as empirical evidence of usability feasibility based on SUS evaluation for an Android-based prototype.